Gestão fiscal e desenvolvimento socioeconômico: uma análise dos municípios maranhenses de 2005 a 2016 - MOREIRA JUNIOR, Walbert Ribeiro (2023)
This work aims to explain the issue of fiscal management and its relationship with socioeconomic development, starting from a review of international and national literature on the subject and culminating in an analysis of data from municipalities in the State of Maranhão. Knowing that several variables can contribute to the socioeconomic development of a municipal entity, this work does not intend to explain all the socioeconomic development of municipalities through fiscal management, but rather to verify specifically how this aspect can influence its development. For this analysis we used the regression model with panel data and application of Granger causality. For municipal fiscal management, as it presents inconsistent data for the analyzed period, public spending on investments was used, and the IFGF is composed of four indicators: autonomy, personnel expenses, liquidity and investments. As for socioeconomic development, all available indicators for the IFDM were used, which include: Employment and Income, Education and Health. In this study, data from the 80 municipalities in Maranhão that showed consistency of the IFGF and IFDM data among the 217 existing municipalities in the state of Maranhão for the time series from 2005 to 2016 were applied. statistical point of view, suggest the influence of development on fiscal management and not the opposite, according to the variables that made up the model.